Hidden affections eaudiobook Hearts along the river series, book 3. - Parr, Delia (Hearts Along the River, 2012)
Having garnered such honors as the Laurel Wreath Award for Historical Romance, CBA best-selling author Delia Parr delivers an engaging tale set in the outskirts of 1830s Philadelphia. While on her way to a new life, Annabelle Tyler finds herself handcuffed by highwaymen to Harrison Graymoor-Philadelphia's most eligible bachelor-and thrust into a marriage neither wants. Before they can annul this sham, however, the newspaper announces their nuptials. As the plot thickens, the unlikely couple desperately tries not to fall in love.